2006
DOI: 10.1021/jp064487v
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Large-Scale Production of ZnO/Zn−Al Layered Double Hydroxide Hierarchical Heterostructures

Abstract: ZnO/Zn-Al layered double hydroxide (ZnO/Zn-Al LDH) hierarchical architecture, a new type of ZnO-based heterostructure, has been synthesized directly on an Al substrate via a facile solution phase process. The firecracker-like heterostructures consist of uniform ZnO nanorods orderly standing at the edges of two-dimensional (2D) surfaces of Zn-Al LDH nanoplatelets. Experimental result obtained from the early growth stage indicates that the underlying Zn-Al LDH nanoplatelet arrays are well constructed with their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
39
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 64 publications
12
39
1
Order By: Relevance
“…20(a) [203,204]. In an alkaline environment, a thin layer of hydrotalcite-like zincowoodwardite plates was first formed as a result of the reaction between zinc and aluminum ions [203,205,206]. Zincowoodwardite belongs to a family of layered compounds with positively charged layers of Zn 2+ and Al 3+ with hydroxide anions, and interlayer charge-balancing anions SO 4 2− .…”
Section: Hierarchical Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…20(a) [203,204]. In an alkaline environment, a thin layer of hydrotalcite-like zincowoodwardite plates was first formed as a result of the reaction between zinc and aluminum ions [203,205,206]. Zincowoodwardite belongs to a family of layered compounds with positively charged layers of Zn 2+ and Al 3+ with hydroxide anions, and interlayer charge-balancing anions SO 4 2− .…”
Section: Hierarchical Structuresmentioning
confidence: 99%
“…Moreover, the thin ZnO seed layer provided a continuous pathway for carrier transport for electronic applications [245,247]. In another report [203], a thin layer of Al was coated onto carbon nanotube so that a hydrotalcite-like zinc aluminum hydroxide interfacial compound formed [205,206], which was very effective in promoting the growth of ZnO nanorods.…”
Section: Zno-carbon Nanotubesmentioning
confidence: 99%
“…It is still a one-step recipe that guarantees quite a good adhesion and morphology [30][31][32]. Instead of adopting dissolved metal salts, one of the two metals is provided as a substrate, which behaves either as a sacrificing element for the film growing on it, or a reacting source of one of the corresponding metal.…”
Section: In Situ Film Growthmentioning
confidence: 99%
“…This is one more one-step method for direct deposition of LDH films with good adhesion and controllable morphology [30][31][32]. It could be considered a sort of modified co-precipitation method in that one of the two metals is not provided by the respective dissolved salt but instead by the substrate itself.…”
Section: In-situ Film Growthmentioning
confidence: 99%
“…In the last decade, different groups [30][31][32] have demonstrated that LDH films can be deposited on metal surfaces by using aluminium or zinc foils as sacrificing substrates for the in-situ growth that is a sort of modified coprecipitation method as described in paragraph 1.3.5. Those studies were mainly addressed applications of LDHs as anticorrosion coatings or functionalized electrodes for electrical batteries and capacitors.…”
Section: Controlled Film Depositionmentioning
confidence: 99%